Non-governmental organisations in the African human rights system: an attempt to systematise the role of NGOs in regional human rights litigation in Africa (African Human Rights Yearbook / Annuaire Africain des Droits de l’Homme, 2023)
Non-governmental organisations are among the most notable actors in the African Human Rights landscape. They were already active at the genesis of the system where they stood out through their advocacy for the adoption of the founding instruments: the African Charter on Human and Peoples' Rights and its Protocols. Their participation in the various mechanisms for the implementation of the rights enshrined in the Charter is also well known. They are involved in both administrative and quasi-judicial and court proceedings. They are also active in litigation and advisory proceedings. This strong presence of NGOs in the African human rights system raises questions about their contribution to the protection of Human Rights in Africa. The purpose of this study is to highlight the contribution of NGOs by systematising their role in the cases brought before the three supervisory bodies. This role is twofold. It consists of a right to report human rights violations to themonitoring bodies and a right to participate in the proceedings before such bodies.
Keywords: organisations non gouvernementales; actio popularis; tierce intervention; amicus curiae; Commission africaine des droits de l’homme et des peuples; Comité africain d’experts sur les droits et le bien-être de l’enfant; Cour africaine des droits de l’homme et des peuples; dénonciation; droits collectifs